Overview of the Prevalence of Patients with Sexually Transmitted Infections at Dr RM Djoelham Binjai Hospital in the Period of January 2019-July 2023 - Ikhwan, Haznur; Hervina (International Journal of Public Health Excellence (IJPHE), 2023)
Sexually Transmitted Infections (STIs) are infections transmitted through vaginal, anal/anal, and oral/oral intercourse. In Indonesia, this disease continues to grow in the community and can cause death. Types of STIs include gonorrhea, non-specific urethritis, syphilis, mole ulcer, inguinal granuloma, lymphogranuloma venereum, bacterial vaginosis, genital herpes, condyloma acuminata, HIV (Human Immunodeficiency Virus), trichomoniasis and candidiasis vulvovaginitis.   The retrospective :descriptive method with a cross sectional design and data collection means is secondary data of new patients diagnosed with STIs and recorded in the Medical Record Sciences of Dr RM Djoelham General Hospital for the period January 2019-July 2023. Results : the prevalence of STI patients, from the diagnosis of the most gonorrhea 27 patients (42.9%), age group 17-25 years 27 patients (42.9%), male sex 39 patients (61.9%) and employment is not ASN (State Civil Apparatus) as many as 20 patients (31.7%) and education is high school graduation / equivalent 29 patients (21.4%). Conclusion: counseling and education are routinely provided to all levels of society. so that this STI is controlled so that morbidity and mortality rates decrease.